Analysis of glucose‐dependent dielectric properties of aqueous‐based solution: A proof of concept - Satish; Kushal Sen; Sneh Anand (IET Science, Measurement & Technology, 2021)
Abstract In spite of widespread research and exploration, the status of non‐invasive blood glucometer for diabetic people is far from satisfactory. This unlocks the prospect for further significant research in the field of non‐invasive blood glucose sensing. An approach towards the research on the development of non‐invasive blood glucometer relies on the establishment of correlation, if any, exists between the dielectric properties of blood and the blood glucose level. In this context, the in‐vitro study is undertaken as a proof of concept using a standard liquid‐dielectric‐test‐fixture. The research is conducted to analyse the variation in dielectric properties of aqueous‐based solution with respect to glucose concentration by utilising test fixture. The employed measurement set‐up and the procedure used for the estimation of dielectric properties (complex‐relative‐permittivity and dissipation factor) of the solution under test are presented. The measurement set‐up is validated by determining the dielectric properties of the reference liquid. The evaluation of uncertainty‐in‐measurement in the complex‐relative‐permittivity and dissipation factor is also provided in detail. However, the variation in dielectric properties is found to be small under tested conditions, and the in‐vitro study conducted out in the perspective of proof of concept has provided an insight that the change in glucose concentration results in quantifiable variation in dielectric properties.